Metallothionein levels on the gill and liver of Mystus nigriceps (Valenciennes, 1840) in Welang River, Pasuruan City, East Java - Lisma Wardani; Endang Yuli Herawati; Asus Maizar Surya (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
This research was conducted in October 2021 using a survey method. Sampling was carried out three times with a span of every 2 weeks at 3 stations along the lower reaches of the Welang River Pasuruan Regency. Parameters observed included cadmium metal content in fish gills and liver, metallothionein levels in gills, and liver of M. nigriceps. Fish and the relationship between cadmium metal and metallothionein levels in the gills and liver of M. nigriceps in the Welang River. The average yield of cadmium metal content in the gills of M. nigriceps is 5.943-8.103 mg/l. Meanwhile, the average result of heavy metal content in the liver of M. nigriceps is 6.397-9.997 mg/l. Measurement of metallothionein levels showed that the average level of metallothionein in the gills of M. nigriceps was 5.860-8.688 ng/mL. Meanwhile, the average level of metallothionein in the liver of M. nigriceps is 7.110-8.334 ng/mL. And the results of the linear regression test showed that the average content of cadmium in the gills and liver with the average metallothionein levels in the gills and liver of catfish was significantly correlated.